Perceived impact of mentoring programme on job satisfaction and performance among metalwork teachers - Ogbuanya, Chinyere Theresa (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2022)
The study determined the perceived impact of mentoring on job performance and satisfaction among metal work teachers in North-West, Nigeria. A quasi-experimental design was used for the study. The sample was made up of 35 teachers drawn from four technical colleges in North West, which comprise of 16 teachers in the experimental group and 19 teachers in the control group. A questionnaire was used for data collection. Three experts validated the instrument and the reliability coefficient was 0.93. The experimental group received the mentoring programme which adapted the four stages of Krams model while the control group was trained with an unplanned and informal method. A pre-test was administered a week before the experiment to both groups followed by the treatment that lasted for 13 weeks. Similarly, post-test was administered to both groups two weeks after the treatment. ANCOVA was used to test the hypothesis. The findings revealed a significant impact of mentoring on job performance and satisfaction, but no significant influence of gender was observed. Hence, it was recommended that technical colleges in Nigeria should adopt the use of mentoring for improving metal work teachers job performance and satisfaction.